Rural-Urban Differentials of Childhood Malnutrition in Bangladesh - Rahman, Azizur; Rahman, Md. Sazedur (International Journal of Child Health and Nutrition, 2019)
Malnutrition is a major health problem in developing countries and it affects childhood growth. Data from the 2014 Bangladesh Demographic and Health Survey were used in this study to explore the rural-urban disparities of malnutrition in children aged 0-59 months. Findings revealed that the prevalence of stunting, underweight and wasting were respectively as 39.6%, 35.7% and 16.7% for the rural children and 32.4%, 27.9% and 13.0% for the urban children. Both moderate and severe malnutrition were significantly higher in rural than urban community, and rural children ran about 1.3 times higher risk of becoming malnourished than their urban counterparts. The height and weight of children, mother’s BMI, parents’ education and family wealth index were found to be the significant factors associated with differentials at rural-urban malnutrition. Appropriate socioeconomic development, antenatal care in pregnancy and poverty reduction programs with a special emphasis on rural community would reduce the overall rural-urban inequality